Garth Welch interviewed by Michelle Potter in the Esso Performing Arts collection - Welch, Garth, 1936-; Potter, Michelle, 1944-; National Library of Australia; Esso Australia; Esso Performing Arts and Oral History Archive Project (1990)
Welch talks about his family background and childhood in Brisbane; his early experience of dance and dance education with Phyllis Danaher; early acting experience; joining the Borovansky Ballet Company in 1954; other ballet artists he worked with and performances with Borovansky. He discusses performing in London and the value of living overseas. He also speaks about working as principal dancer in the Australian Ballet Company and under Robert Helpmann's choreography; his Harkness Fellowship; beginning as a choreographer; contact with Rudolf Nureyev; moving to Ballet Victoria and on to West Australia Ballet Company as artistic director; his role as Zac in "A Chorus Line"; and his sons who have both become dancers. He speaks about dancing again in "After Venice" with Sydney Dance Company; directing "Othello" in Manila; his current work "In Praise of Folly" and his views on the future of Australian dance.
Part of a collection of oral history interviews produced by the Esso Performing Arts and Oral History Archive Project.
Recorded at the National Library, Canberra, Australian Capital Territory on January 31, 1990.
Digital master available
Transcript available (typescript 101 p.)
Keywords: Welch, Garth, -- 1936- -- Interviews; Ballet -- Australia; Ballet dancers -- Australia -- Biography